Description of eight new species of Ixodes Latreille, 1795 (Acari: Ixodidae) and redescription of I. auritulus Neumann, 1904, parasites of birds in the Australasian, Nearctic and Neotropical Regions - Apanaskevich, Dmitry A.; Apanaskevich, Maria A.; Klimov, Pavel B.; Edgy, Brett M.; Bermúdez, Sergio E.; Labruna, Marcelo B.; Korzeev, Andrei I.; Barker, Stephen C. (Zootaxa, 2022)
Ixodes brevisetosus n. sp. from Papua New Guinea, Ixodes contrarius n. sp. from Costa Rica, Ixodes guglielmonei n. sp. from Argentina and Chile, Ixodes insulae n. sp. from Australia, Ixodes moralesi n. sp. from Guatemala and Panama, Ixodes rio n. sp. from Brazil, Ixodes robbinsi n. sp. from Canada and the United States and Ixodes tinamou n. sp. from Peru (Acari: Ixodidae) are described based on females, nymphs and larvae from various avian hosts (Charadriiformes: Charadriidae; Falconiformes: Falconidae; Galliformes: Cracidae, Odontophoridae, Phasianidae; Passeriformes: Acanthizidae, Cardinalidae, Emberizidae, Fringillidae, Furnariidae, Melanocharitidae, Orthonychidae, Paridae, Passeridae, Petroicidae, Thamnophilidae, Troglodytidae, Turdidae; Strigiformes: Strigidae; Tinamiformes: Tinamidae) and a rodent (Rodentia: Muridae). Females, nymphs and larvae of all new species are similar to those of Ixodes auritulus Neumann, 1904, but can be distinguished by the shape of the scutum and basis capituli, relative length of idiosomal setae, auriculae and internal projection on palpal segment I, degree of development of dorsoapical and mesodorsal spurs on palpal segment I, and measurements and proportions of various structures. Females, nymphs and larvae of I. auritulus s. str. are redescribed based on specimens from passerine birds (Furnariidae, Troglodytidae, Turdidae) in Chile. The subspecies I. auritulus zealandicus Dumbleton, 1961 is elevated to species status, Ixodes zealandicus Dumbleton, 1961. Based on our extensive survey and morphological analyses, we evaluate the actual species richness in the I. auritulus species group and discuss future directions in the systematics of this group of ticks.